Blended Learning with the Flipped Classroom Method: A Post-Pandemic Solution and Future Trend - Zulaikhah, Siti; Hasanah, Ida Faridatul; Sutiyono, Agus; Rohmat, Rohmat; Wibowo, Gita Vallenti (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
Technological advancements have significantly impacted various aspects of life, particularly education. The Covid-19 pandemic, which lasted for over two years, further disrupted the education sector, necessitating a shift in teaching and learning practices. New policies, often referred to as the "new normal," have brought changes that allow educational activities to resume as they were before the pandemic. This study explores learning solutions during the new normal and investigates future trends focusing on blended learning integrated with the flipped classroom method. The research was conducted at FTK Raden Intan Lampung using a case study methodology with a single-case design. Data were collected through observations, documentation, and interviews centered on the implementation of the blended learning model combined with the flipped classroom approach. The findings indicate that this model encourages students to engage in active, independent learning, enhances learning satisfaction, and holds potential as a future learning trend. In conclusion, the blended learning model utilizing the flipped classroom method emerges as an effective post-pandemic learning alternative. It offers convenience, fosters enthusiasm for learning, and enhances students' problem-solving abilities throughout the learning process.